A case of seminal vesicle metastasis from bilateral seminoma - Yusuke Aida; Yosuke Yasuda; Emiko Sugawara; Kosuke Takemura; Yusuke Yoneoka; Ryo Fujiwara; Tomohiko Oguchi; Noboru Numao; Junji Yonese; Takeshi Yuasa (IJU Case Reports, 2025)
Introduction Postoperative recurrence of seminoma is often seen in lungs, liver, and retroperitoneal lymph nodes, such as the para‐aortic lymph nodes. Most of these recurrences (>90%) occur in the first 3 years after orchiectomy. We report a case of a single recurrence in the seminal vesicle after bilateral radical orchiectomies for metachronous bilateral testicular seminoma. Case presentation A 52‐year‐old patient with a past history of bilateral testicular seminoma was diagnosed with left seminal vesicle metastasis by magnetic resonance imaging followed by needle biopsy 8 years after the first orchiectomy. After four cycles of bleomycin, etoposide, and cisplatin regimen were administered, FDG‐18 positron emission tomography‐computed tomography showed no abnormal signal in the left seminal vesicle. Conclusion To the best of our knowledge, this is the first report of seminal vesicle metastasis following radical orchiectomies for bilateral testicular seminoma.